Toksisitas Merkuri (Hg) pada struktur jaringan ikan - Ibrahim, Tamrin A.; Aris, Muhammad (e-Journal BUDIDAYA PERAIRAN, 2021)
The problem of pollution that occurs in the aquatic environment is getting out of control and causes the degradation of fishery resources which are important for humans. One of the pollutants from industrial activities is heavy metal. There are various kinds of heavy metals, mercury (Hg) is the most dangerous heavy metal. Mercury (Hg) enters directly into the waters through rainwater and leaching the soil and river flows which are then absorbed and metabolized by microorganisms. Mercury (Hg) is difficult to degrade from the body, because mercury (Hg) is actively involved in the food chain. Microorganisms feed molluscs, crustaceans and fish which are a source of protein for humans. Mercury (Hg) toxicity in fish can result in a stress response in fish which results in impaired growth, immune system, and changes in tissue structure. This brief review aimed to enrich the scientific repertoire of the toxicity of mercury (Hg) in fish and its effects on humans. This review was a non-experimental research by conducting research around the literature